The Profile of Student Analytical Skills through Hypothetical Learning Trajectory on Colligative Properties Lesson - Akbar, Said Ali; Hasby, Hasby (SCAD Independent, 2019)
Students often have difficulty in understanding chemistry lessons, especially Colligative Properties. Teachers should have systematic learning plans so that students understand the content of learning well. Hypothetical Learning Trajectory (HLT) is effective to be used in the learning process because it becomes an idea in designing detailed learning paths. Besides that, learning outcomes can be achieved well and optimally. This study uses qualitative and quantitative approaches. Data processing is carried out based on four assessment criteria. First, student responses that appear based on response predictions, second, student ability test scores, third, analysis of learning activities, and finally science process skills (SPS). The results showed that the didactic presented by the teacher as a student learning path was good enough. Only 12% of student responses are beyond predictions. Furthermore, student SPS through the use of HLT shows that classification and communication skills have a high value, respectively 82% and 81%. Meanwhile, based on Piaget's approach, students' conceptual abilities are better (56%), compared to other abilities. Therefore, the application of HLT to the material of colligative properties towards students is very good.